Simulation-based risk assessment of sUAV-car collision - Hu, Haoliang (Nanyang Technological University, 2021)
The use of small unmanned aerial vehicles (sUAVs) in urban area increases significantly in recent years. However, when sUAVs are being operated in urban areas, cars on the ground will be at certain risk due to being exposed to the possible crashing sUAVs, thus the ground risk assessment is critical to reduce ground casualties caused by UAV failures. This study propose a simulation-based method to estimate such risk. At first, ADAMS and MATLAB co-simulation was used to estimate the impact risks area, investigated the effects of different sUAV failure modes to the crash trajectories, crash velocities and then determined the possible coverage of crash on the ground. Then, ABAQUS utilized to analyze the collision simulation of the sUAV and the car at different impact speeds and different road conditions. Depending on the damage from collision simulation, the collision velocity range of the risk caused by the sUAVs impacting were determined. Finally, a risk assessment was conducted on sUAVs and ground vehicles, the Equivalent level of safety and third-party risks were determined and proposed the concept of establishing corresponding drone electronic fences in urban areas.